Digital Model of the Turgoyak Lake System, Southern Urals - I. Yu. Chernova; L. R. Kosareva; N. G. Nourgalieva; O. S. Chernova (Georesursy, 2025)
The sediments of Lake Turgoyak (Southern Urals, Russia) have been accumulating throughout the Late Pleistocene and the Holocene. Sedimentation is controlled by the lake’s morphometry, drainage systems, vertical zoning, thermal state of the water, and wind action.Therefore, analysis of cartographic materials illustrating the area’s geology, topography, drainage systems, watersheds (catchment areas) and drainage divides is relevant in this regard. All these aspects are important for assessing the role of sediment sources and transportation routes, as well as deposition mechanisms and sediment distribution within the lake. The study of lake deposits provides valuable insights for genetic interpretation of sedimentary sequences in the context of paleoclimatic and paleoecological trends and events.This study presents a digital model of Lake Turgoyak and its surroundings. The model was developed using GIS software, incorporating available geological, topographical, and bathymetric maps. Overlaying watershed models onto geological maps of pre-Quaternary and Quaternary deposits enabled assumptions about the material composition of sediment transported into the lake.Developing similar digital models for lake systems in the Urals, other regions of Russia, and worldwide opens opportunities to systematize information at a new level and utilize it for various reconstructive purposes.